Strain-Specificity and Disease-Specificity of Probiotic Efficacy: A Systematic Review and Meta-Analysis - McFarland, Lynne V.; Evans, Charlesnika T.; Goldstein, Ellie J. C. (Frontiers in Medicine, 2018)
Background. As the use and diversity of probiotic products expands, the choice of an appropriate type of probiotic is challenging for both medical care professionals and the public alike. Two vital factors in choosing the appropriate probiotic are often ignored, namely the probiotic strain-specificity and disease-specificity for efficacy. Reviews and meta-analyses often pool together different types of probiotics, resulting in misleading conclusions of efficacy. Methods. A systematic review of the literature (1970-2017) assessing strain-specific and disease-specific probiotic efficacy was conducted. Trials were included for probiotics with an identifiable strain (either single strain or mixtures of strains) that had at least two randomized, controlled trials for each type of disease indication. The goal was to determine if probiotic strains have strain and/or disease specific efficacy. Results. We included 228 trials and found evidence for both strain specificity and disease specificity for the efficacy of specific probiotic strains. Significant efficacy evidence was found for 7 (70%) of probiotic strain(s) among four preventive indications and 11 (65%) probiotic strain(s) among five treatment indications. Strain-specific efficacy for preventing adult AAD was clearly demonstrated within the Lactobacillus species [e.g., by the mixture of L. acidophilus CL1285, L. casei LBC80R and L. rhamnosus CLR2 (Bio-K+®), by L. casei DN114001 (Actimel®) and by L. reuteri 55730], while other Lactobacillus strains did not show efficacy. Significant disease-specific variations in efficacy was demonstrated by Lactobacillus rhamnosus GG and Saccharomyces boulardii CNCM I-745, as well as other probiotic strains. Conclusions. Strong evidence was found supporting the hypothesis that the efficacy of probiotics is both strain-specific and disease-specific. Clinical guidelines and meta-analyses need to recognize the importance of reporting outcomes by both specific strain(s) of probiotics and the type of disease. The clinical relevance of these findings indicates healthcare providers need to take these two factors into consideration when recommending the appropriate probiotic for their patient.